Hubungan Kepatuhan Pasien Mengontrol Aktivitas Olahraga, Merokok Dan Berat Badan Dengan Kejadian IMA Recurrent - Rosmin Ilham; Elvie F Dungga (Jurnal Kesehatan Panrita Husada, 2020)
Coronary heart disease can generally recur, if the cause cannot be controlled, recurrent events in myocardial infarction are called acute recurrent myocardial infarction due to uncontrolled risk factors or patient non-compliance in undergoing rehabilitation therapy. The purpose of this study was to determine the relationship of patient compliance controlling sports activities, smoking, and body weight with the incidence of recurrent IMA in Gorontalo city hospitals. This research uses Analytical Survey design with a Cross-Sectional approach. The population in this study were all IMA patients in Gorontalo City Hospital. Samples totaled 36 respondents using accidental sampling technique. The statistical analysis used was the Chi-square Test and Fishers' Exact Test. The results showed that there was no significant relationship between patient compliance controlling sports activities (p = 0.255), smoking (p = 0.676), and weight (0.357) with the incidence of Recurrent IMA in Gorontalo City Hospital. The conclusion in this study is that there is no significant relationship between adherence to control sports activities, smoking, bodyweight with the incidence of IMA Recurrent in Gorontalo City Hospital.